A novel technique to treat dysphagia after endoscopic full-thickness plication for managing gastroesophageal reflux disease - Patil, Gaurav; Iyer, Arun; Dalal, Ankit; Maydeo, Amit (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Patil G, Iyer A, Dalal A, Maydeo A. A novel technique to treat dysphagia after endoscopic full-thickness plication for managing gastroesophageal reflux disease. Turk J Gastroenterol 2020; 31(9): 671-2.